The correlation among student's anger, aggression and student's performance - Duru, Batu (Int Scientific Conference SGEM, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2011)
The aim of this paper is to review and identify the correlation among students' anger, aggression and students' performance. These concepts also have an important role in one's daily life. This research aimed at exploring the relationship among students' anger, aggression and students' performance inventories. To this end, a research has been conducted on the students of vocational studies (n=184) in Istanbul. According to the results, a weak relationship (r<0,38) was revealed between students' anger and academic performance. On the other hand, there is a strong relationship (r>0,63) between students' aggression and academic performance.
Keywords: Performance; anger; education; aggression